Search methods for prognostic factor systematic reviews: a methodologic investigation - Boulos, Leah; Ogilvie, Rachel; Hayden, Jill A. (Journal of the Medical Library Association, 2021)
Objective: This study retroactively investigated the search methods used in the 2019 Hayden et al. study, one of the first systematic reviews of prognostic factors that was published in the Cochrane Library. The review was designed to address recognized weaknesses in reviews of prognosis by using multiple supplementary search methods in addition to traditional electronic database searching.Methods: The authors used four approaches to comprehensively assess aspects of systematic review literature searching for prognostic factor studies: (1) comparison of search recall of broad versus focused electronic search strategies, (2) linking of search methods of origin for eligible studies, (3) analysis of impact of supplementary search methods on meta-analysis conclusions, and (4) analysis of prognosis filter performance.Results: The review’s focused electronic search strategy resulted in a 91% reduction in recall, compared to a broader version. Had the team relied on the focused search strategy without using supplementary search methods, they would have missed 23 of 58 eligible studies that were indexed in MEDLINE; additionally, the number of included studies in 2 of the review’s primary outcome meta-analyses would have changed. Using a broader strategy without supplementary searches would still have missed 5 studies. The prognosis filter used in the review demonstrated the highest sensitivity of any of the filters tested.Conclusions: Our study results support recommendations for supplementary search methods made by prominent systematic review methodologists. Leaving out any supplemental search methods would have resulted in missed studies, and these omissions would not have been prevented by using a broader search strategy or any of the other prognosis filters tested.